2017
DOI: 10.3389/fmicb.2017.01598
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Changes Exhibited by E. coli Cultured in Space

Abstract: Bacteria will accompany humans in our exploration of space, making it of importance to study their adaptation to the microgravity environment. To investigate potential phenotypic changes for bacteria grown in space, Escherichia coli was cultured onboard the International Space Station with matched controls on Earth. Samples were challenged with different concentrations of gentamicin sulfate to study the role of drug concentration on the dependent variables in the space environment. Analyses included assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 39 publications
10
80
0
Order By: Relevance
“…These methods have successfully been used to predict the morphological and physiological responses of microorganisms to microgravity. The results obtained for Staphylococcus mutans, Escherichia coli, Mycobacterium marinum, and Streptomyces coelicolor under these conditions have been proved to be consistent with those found on the ISS (18)(19)(20)(21)(22). However, inconsistent results were also found in several studies when different bacteria, experimental setups, and cultivation conditions were used (23).…”
supporting
confidence: 71%
“…These methods have successfully been used to predict the morphological and physiological responses of microorganisms to microgravity. The results obtained for Staphylococcus mutans, Escherichia coli, Mycobacterium marinum, and Streptomyces coelicolor under these conditions have been proved to be consistent with those found on the ISS (18)(19)(20)(21)(22). However, inconsistent results were also found in several studies when different bacteria, experimental setups, and cultivation conditions were used (23).…”
supporting
confidence: 71%
“…Nevertheless, significant knowledge gaps remain to be addressed. This study describes the results of transcriptomic analyses that enabled determining the differentially expressed genes on samples at different gravitational regimes and concentrations of drug, and complements previous work ( Zea et al, 2016 , 2017 ) based on data from the same spaceflight experiment [Antibiotic Effectiveness in Space (AES-1)]. Specifically, this current study focuses on expression patterns and possible interaction of E. coli stress regulators associated primarily with oxidative and antibiotic stress, and examines how exposure to microgravity influences those regulatory interactions ( Figure 1A ).…”
Section: Introductionmentioning
confidence: 56%
“…Spaceflight has been shown to promote biofilm formation in bacteria, which may pose challenges involving biofouling, corrosion, the contamination of water sources, and increased bacterial virulence ( McLean et al, 2001 ; Kim et al, 2013 ; Ott et al, 2016 ). Changes of microbial behavior observed in space include improved growth ( Zea et al, 2017 ), decreased susceptibility to antibiotics ( Tixador et al, 1985 ; Lapchine et al, 1986 ; Moatti et al, 1986 ; Tixador et al, 1994 ; Klaus and Howard, 2006 ; Kitts et al, 2007 ; Parra et al, 2008 ; Ricco et al, 2010 ), enhanced capability to form biofilms ( McLean et al, 2001 ; Kim et al, 2013 ), formation of outer membrane vesicles ( Zea et al, 2017 ), and increased virulence ( Wilson et al, 2007 , 2008 ), to name a few. In the case of cultures grown in liquid medium, some of these responses may result from an altered extracellular environment in space in which mass transport is limited to diffusion due to the lack of gravity driven forces, as was recently corroborated by a molecular genetic study ( Zea et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, changes in the biofilm formation ability are probably associated with changes in growth rates (Farshadzadeh et al, ). Zea et al () reported that E. coli cells in space accounted for 37% of the volume of the control group. Additionally, Mauclaire and Egli () reported that two ISS isolates ( Micrococcus luteus strains LT110 and LT100) produced significantly fewer extracellular polysaccharides under simulated microgravity, similar to that observed in a low shear stress environment, compared with normal gravity.…”
Section: Discussionmentioning
confidence: 99%